Digitalization of the accounting profession: An assessment of digital competencies in a Malaysian comprehensive university / Azuraidah Taib ... [et al.] - Taib, Azuraidah; Awang, Yunita; Mohamed Shuhidan, Shazalina; Zainal Zakaria, Zaiza Norsuriati; Sri Sulistyowati, Sri Sulistyowati; Luluk Muhimatul Ifada, Luluk Muhimatul Ifada (Universiti Teknologi MARA, 2023)
Most professions will change or disappear altogether as a result of digitalization. While some professions will disappear completely, others will continue to grow, and it is also possible that additional professions will emerge in the future that we do not currently know about. Numerous technological advances impacting the accounting industry are forcing accountants to acquire essential digital skills and competencies to ensure their survival. This study, therefore, seeks to investigate the level of digital competencies among postgraduate accounting students. Online questionnaires were distributed to 440 registered postgraduate accounting students in a Malaysian comprehensive university. Mean analysis shows moderate to high scores on items measuring the components of digital competence. In addition, the results show a positive moderate relationship between media literacy and digital literacy, while a positive strong relationship was found between information literacy, information and communication technology literacy, and digital literacy with digitalization. The results shed light on the level of digital competencies of accounting students after graduation, which helps to assess how digital competencies affects the digitization of the accounting profession. Future research could be extended to include students from other universities and accounting practitioners to improve the research findings.